2020
DOI: 10.1002/da.22998
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical impairment of subthreshold PTSD using DSM‐5 criteria in a national sample of Korean firefighters

Abstract: Background Firefighters are at high risk for subthreshold and full‐threshold posttraumatic stress disorder (PTSD) due to their frequent exposure to various traumatic events. Although individuals with subthreshold PTSD have increased impairment, often needing treatment, the rates of subthreshold PTSD in firefighters remain unknown. Moreover, there is currently no consensus regarding the definition of subthreshold PTSD. The purpose of this study was to investigate the rates and clinical impairment of subthreshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
2
15
1
Order By: Relevance
“…For symptomatology, several symptoms of the diagnostic criteria for PTSD may overlap with those of depression and anxiety disorders (Pietrzak et al, 2011). Unlike previous studies that have reported higher odds ratios for alcohol abuse in individuals with subthreshold PTSD (R. E. Adams et al, 2006; Jeon et al, 2007; Kim et al, 2020), we found no association between subthreshold PTSD and alcohol use disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…For symptomatology, several symptoms of the diagnostic criteria for PTSD may overlap with those of depression and anxiety disorders (Pietrzak et al, 2011). Unlike previous studies that have reported higher odds ratios for alcohol abuse in individuals with subthreshold PTSD (R. E. Adams et al, 2006; Jeon et al, 2007; Kim et al, 2020), we found no association between subthreshold PTSD and alcohol use disorders.…”
Section: Discussioncontrasting
confidence: 99%
“… 80 For instance, a Korean cross‐sectional study of 45 698 current firefighters found a prevalence of PTSD according to DSM‐5 criteria of 2.6% and subthreshold PTSD defined by 6 different sets of symptoms in 1.8–18%. 81 Subthreshold PTSD by all definitions was significantly associated with suicidal behavior, depression, alcohol use problems, and functional impairment—even in the most relaxed definitions of subthreshold PTSD based upon at least one DSM‐5 symptom from each of the five symptom clusters, B‐F rated 2 or higher (moderately to extremely). Similarly, McLaughlin et al found that the presence of two DSM‐5 symptoms from any of the symptom clusters was strongly related to clinically significant distress or impairment and comorbid disorders with odds ratios 9.7 (95% CI 2.2–42.7) and 3.0 (95% CI 1.7–5.2), respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Subthreshold PTSD symptoms may indicate clinically significant distress and functional impairment. Findings from a Korean cross-sectional study among 45,698 active firefighters indicated that the presence of subthreshold PTSD symptoms was associated with suicidal behavior, depression, alcohol use problems, and functional impairment[ 48 ]. Assessment of a history of TBI is mandatory in help-seeking, trauma-exposed individuals, specifically in soldiers and veterans, who are at increased risk of PTSD with delayed expression[ 2 - 4 ].…”
Section: Discussionmentioning
confidence: 99%